Bonding strategies to full-contour zirconia: Zirconia pretreatment with piranha solution, glaze and airborne-particle abrasion - Feitosa, Sabrina A. [UNESP]; Lima, Nelson B.; Yoshito, Walter K.; Campos, Fernanda [UNESP]; Bottino, Marco A. [UNESP]; Valandro, Luiz F.; Bottino, Marco C. (Elsevier, 2017)
This study aimed to evaluate the effect of various zirconia surface pretreatments on the adhesion between full contour 3Y-TZP zirconia and glaze, and the shear bond strength (SBS) between glazed/3Y-TZP and resin cement. Specimens were allocated into groups: GL-glaze; AL+GL-sandblasting with Al2O3+GL; CJ+GL-tribochemical silica coating (Cojet®/CJ)+GL; PS+GL-piranha solution+GL; and CJ. Adhesion between 3Y-TZP and GL was evaluated using the scratch test. Surface topography and glaze thickness were evaluated by using a scanning electron microscope (SEM). For SBS, glazed/3Y-TZP surface was etched with hydrofluoric acid and a silane was applied. For CJ only the silane was applied. Samples were tested after 24 h (24 h wet) or after 15,000 thermal cycles and 90 days storage (thermocycled). After SBS, the type of failure was classified as: adhesive, mixed or cohesive. The data were analyzed using two-way ANOVA and Tukey's test. SEM analysis after scratch test revealed circular cracks in the GL group and conformal cracks in the others groups. SEM micrographs suggested that zirconia specimens submitted to airborne-particle abrasion presents rougher and porous surface when compared to surfaces treated with GL and PS. The glaze layer was approximately 1.86 µm thick in all groups. After 24 h, SBS test showed highest values for AL+GL and CJ+GL and were significantly higher when compared to the GL group. Differences were not significant between PS+GL and the other groups. After aging (thermocycling+storage), groups GL and CJ presented no statistically significant difference compared to 24 h and aged AL+GL, CJ+GL and PS+GL groups. The predominant type of failure was mixed. 3Y-TZP surface treatment with glaze application could be considered as an alternative treatment, since it yielded a similar resin bond strength without the need for airborne-particle abrasion.
Keywords: Glaze; Piranha solution; Scratch test; Shear test; Surface treatment; Zirconia